Odor and VOC Emissions from Pan Frying of Mackerel at Three Stages: Raw, Well-Done, and Charred - Ahn, Jeong-Hyeon (Int J Environ Res Public Health, 2014)
Many classes of odorants and volatile organic compounds that are deleterious to our wellbeing can be emitted from diverse cooking activities. Once emitted, they can persist in our living space for varying durations. In this study, various volatile organic compounds released prior to and during the pan frying of fish (mackerel) were analyzed at three different cooking stages (stage 1 = raw (R), stage 2 = well-done (W), and stage 3 = overcooked/charred (O)). Generally, most volatile organic compounds recorded their highest concentration levels at stage 3 (O), e.g., 465 (trimethylamine) and 106 ppb (acetic acid). In contrast, at stage 2 (W), the lowest volatile organic compounds emissions were observed. The overall results of this study confirm that trimethylamine is identified as the strongest odorous compound, especially prior to cooking (stage 1 (R)) and during overcooking leading to charring (stage 3 (O)). As there is a paucity of research effort to measure odor intensities from pan frying of mackerel, this study will provide valuable information regarding the management of indoor air quality.